Using focus groups to improve nursing satisfaction. Issue 3 (March 2020) - Nelson, Alexandra; Frankenberger, Warren D.
Abstract : Learn about how an inpatient pediatrics unit used a collaborative process to gather feedback from RNs and positively impact engagement.